2020
DOI: 10.1111/jnu.12579
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Perceived Value of Certification Among Registered Nurses? A Systematic Review

Abstract: Purpose To explore how registered nurses (certified, noncertified, and managers) value certification as determined by the Perceived Value of Certification Tool, review the psychometric properties of the instrument, and ascertain the benefits and barriers to nursing specialty certification. Design Systematic review (without meta‐analysis) of 18 studies representing 26,534 registered nurses. Methods Rigorous processes were used to minimize bias; to identify, appraise, and synthesize studies to explore how regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, in a study of administrative perioperative nurses, findings also demonstrated that those in administrator/manager roles perceived significantly greater value in certification than did certificants in staff nurse roles 15. In a systematic review, the level of agreement with intrinsic and extrinsic value statements between nurse managers and certified nurses was evaluated 19. Responses of the nurse managers indicated a higher level of agreement than nonmanagerial certified nurses for increased marketability, promoting peer recognition, promoting recognition from other healthcare professionals, and promoting recognition from employers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study of administrative perioperative nurses, findings also demonstrated that those in administrator/manager roles perceived significantly greater value in certification than did certificants in staff nurse roles 15. In a systematic review, the level of agreement with intrinsic and extrinsic value statements between nurse managers and certified nurses was evaluated 19. Responses of the nurse managers indicated a higher level of agreement than nonmanagerial certified nurses for increased marketability, promoting peer recognition, promoting recognition from other healthcare professionals, and promoting recognition from employers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on the characteristics of certified nurses, participants were more likely to become certified if they had a Bachelor of Science in Nursing or higher degree, were older, and more experienced. 18 In addition, medical-surgical areas were less likely to have certified nurses, whereas a high percentage of certified nurses worked in the operating room or oncology. In contrast, this study demonstrated that more than 50% of stroke and neuroscience nurses worked in critical care/medical-surgical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that in the surgical field, not only the development of technological competencies should be prioritized, but also competencies related to care and specialized knowledge [21,22]. The regulated acquisition of these competences, the experience and the continuous training within the clinical field [23,24] are the tools the professional can count on to promote a culture of safety within the surgical field.…”
Section: Discussionmentioning
confidence: 99%